Mitochondrial Iron Transporters (MIT1 and MIT2) Are Essential for Iron Homeostasis and Embryogenesis in Arabidopsis thaliana - Jain, Anshika; Dashner, Zachary S.; Connolly, Erin L. (Frontiers in Plant Science, 2019)
Iron (Fe) is an essential nutrient for virtually all organisms, where it functions in critical electron transfer processes, like those involved in respiration. Photosynthetic organisms have special requirements for Fe due its importance in photosynthesis. While the importance of Fe for mitochondria- and chloroplast-localized processes is clear, our understanding of the molecular mechanisms that underlie the trafficking of Fe to these compartments is not complete. Here, we describe the Arabidopsis mitochondrial iron transporters, MIT1 and MIT2, that belong to the mitochondrial carrier family (MCF) of transport proteins. MIT1 and MIT2 display considerable homology with known mitochondrial Fe transporters of other organisms. Expression of MIT1 or MIT2 rescues the phenotype of the yeast mrs3mrs4 mutant, which is defective in mitochondrial iron transport. Although the Arabidopsis mit1 and mit2 single mutants do not show any significant visible phenotypes, the double mutant mit1mit2 displays embryo lethality. Analysis of a mit1–/mit2+- line revealed that MIT1 and MIT2 are essential for iron acquisition by mitochondria and proper mitochondrial function. In addition, loss of MIT function results in mislocalization of Fe, which in turn causes upregulation of the root high affinity Fe uptake pathway. Thus, MIT1 and MIT2 are required for the maintenance of both mitochondrial and whole plant Fe homeostasis, which, in turn, is important for the proper growth and development of the plant.